Accounting transparencies and audit fees of auditor-designated mutual savings banks in Korea - Hyoun Song; Kyunbeom Jeong (Cogent Business & Management, 2022)
In 1998, the act on mutual savings banks was amended to create a legal basis for auditor designation for certain mutual savings banks in Korea. Also, a series of restructuring processes for the savings banking industry took place in 2011 due to the insolvency of some savings banks. This study empirically analyzes whether the auditor designation rule has affected how mutual savings banks set aside allowance for bad debts and thus help improve their accounting transparency (better asset quality and less earnings management), as well as the impact of this rule on audit fees. It also looks into whether there is any notable difference in accounting transparency and audit fees between before and after the savings bank incident in 2011. We specifically set the six hypotheses about the effect of auditor designation on asset quality, earnings management, and audit fees, and the different effect of savings bank incident on these three factors. We investigate the hypotheses using regression models with 809 firm-year sample from 2005 to 2014. The results show that asset quality has improved for auditor designated mutual savings banks and after the incident. With respect to earnings management, mutual savings banks with designated auditors are found to be less likely to manage their earnings using allowance for bad debts, but there is no statistical significance in difference between before and after the savings bank incident. As for audit fees, the amount of fees is large for auditor-designated mutual savings banks, and after the incident. This study would offer useful insights to financial regulators, auditors, audit clients, and other stakeholders.